(untitled) (Bangladesh Journal of Pharmacology, 2017)
The aim of the present study was to investigate two pharmaceutical groups including fentanyl-midazolam and midazolam-ketamine used as patient seda-tion analgesia for the orthopedic emergency procedures. This is a prospective randomized double-blind and placebo-controlled trial study. Trauma patients admitted to emergency department who needed emergency reduction were enrolled. Finally 81 patients with mean age of 31.7 ± 20.6 years old were participated (64.2% male). It is likely that the combination of midazolam-ketamine had a better performance in terms of the duration of hypoxia (p=0.01), and pain scores during reduction (p=0.001). However, adverse effects were higher in the midazolam-ketamine group compared to the fentanyl-midazolam. The level of satisfaction of physicians and patients were the same.